Seasonal presence and potential influence of humpback whales on wintering Pacific herring populations in the Gulf of Alaska. (January 2018) - Straley, Janice M.; Moran, John R.; Boswell, Kevin M.; Vollenweider, Johanna J.; Heintz, Ron A.; Quinn II, Terrance J.; Witteveen, Briana H.; Rice, Stanley D.
Abstract: This study addressed the lack of recovery of Pacific herring ( Clupea pallasii ) in Prince William Sound, Alaska, in relation to humpback whale ( Megaptera novaeangliae ) predation. As humpback whales rebound from commercial whaling, their ability to influence their prey through top-down forcing increases. We compared the potential influence of foraging humpback whales on three herring populations in the coastal Gulf of Alaska: Prince William Sound, Lynn Canal, and Sitka Sound (133–147°W; 57–61°N) from 2007 to 2009. Information on whale distribution, abundance, diet and the availability of herring as potential prey were used to correlate populations of overwintering herring and humpback whales. In Prince William Sound, the presence of whales coincided with the peak of herring abundance, allowing whales to maximize the consumption of overwintering herring prior to their southern migration. In Lynn Canal and Sitka Sound peak attendance of whales occurred earlier, in the fall, before the herring had completely moved into the areas, hence, there was less opportunity for predation to influence herring populations. North Pacific humpback whales in the Gulf of Alaska may be experiencing nutritional stress from reaching or exceeding carrying capacity, or oceanic conditions may have changed sufficiently to alter the prey base. Intraspecific competition for food may make it harder for humpback whales to meet their annual energetic needs. To meet their energetic demands whales may need to lengthen their time feeding in the northern latitudes or by skipping the annual migration altogether. If humpback whales extended their time feeding in Alaskan waters during the winter months, the result would likely be an increase in herring predation.